Transmission of Amblyomma maculatum-Associated Rickettsia spp. During Cofeeding on Cattle - Lee, Jung Keun (Vector Borne Zoonotic Dis, 2018)
Amblyomma maculatum is the primary vector for the spotted fever group rickettsiae, Rickettsia parkeri, a known pathogen, and “Candidatus Rickettsia andeanae,” currently considered nonpathogenic. Spotted fever group rickettsiae are typically endothelial cell associated and rarely circulate in the blood. Horizontal transmission to naïve ticks through blood feeding from an infected host is likely rare. Cofeeding provides an opportunity for rickettsial transmission to naïve ticks in the absence of circulating rickettsiae. We evaluated R. parkeri transmission through cofeeding between A. maculatum adults and nymphs on beef calves. Six calves in each of two trials were infested with A. maculatum that had been capillary fed R. parkeri. Four days later, calves each received recipient A. maculatum that were either capillary fed “Ca. R. andeanae” or not capillary fed before infestation. Trials differed by whether we included a barrier to minimize adjacent feeding between recipient and donor ticks. After cofeeding, we detected R. parkeri in 27% of “Ca. R. andeanae”-free recipient ticks, whereas R. parkeri was not detected in any recipient ticks that were capillary fed “Ca. R. andeanae.” Rickettsia parkeri transmission efficiency to naïve ticks was greater when ticks freely cofed in proximity. No rickettsial DNA was detected in calf blood. Results confirm cofeeding as a method of horizontal transmission of R. parkeri in the absence of host rickettsemia and suggest no evidence of transmission by cofeeding when recipient ticks are first exposed to “Ca. R. andeanae” through capillary feeding. While cofeeding may provide an opportunity for maintaining the pathogen, R. parkeri, the mechanisms driving any potential effect of “Ca. R. andeanae” on R. parkeri transmission are unclear.